The effect of arbuscular mycorrhizal colonisation on the C economy, growth and nutrition of young grapevines - Mortimer, Peter Edward (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2004.